2021
DOI: 10.1186/s12889-021-11100-4
|View full text |Cite
|
Sign up to set email alerts
|

Medicine storage, wastage, and associated determinants among urban households: a systematic review and meta-analysis of household surveys

Abstract: Background Irrational household storage of medicines is a world-wide problem, which triggers medicine wastage as well as its associated harms. This study aimed to include all available evidences from literature to perform a focused examination of the prevalence and factors associated with medicine storage and wastage among urban households. This systematic review and meta-analysis mapped the existing literature on the burden, outcomes, and affective socio-economic factors of medicine storage am… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 94 publications
2
27
0
2
Order By: Relevance
“…In a systematic review, the prevalence of medicine storage was 35 to 100%, and the wastage of medicine was 17%. This review also stated that southwest region of Asia has the highest rate of drug storage and wastage among urban households [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a systematic review, the prevalence of medicine storage was 35 to 100%, and the wastage of medicine was 17%. This review also stated that southwest region of Asia has the highest rate of drug storage and wastage among urban households [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis showed that the prevalence of storing medicines in houses was 77% [ 31 ]. In our study also only 88 (41.9%) participants said that they rarely store unused medications while 91.9% believed that storing excess medicines at home may promote self-medication.…”
Section: Discussionmentioning
confidence: 99%
“…A national survey on the use of medication by Malaysian consumers in 2015 reported that despite extensive use of pharmaceuticals, 18.6% of respondents did not fully understand how to properly use their medication, and 17.0% had no knowledge regarding proper medication storage [ 2 ]. Underutilization and nonadherence coupled with poor knowledge of medication management could be contributing factors to treatment failure and wasted resources [ 3 ].…”
Section: Introductionmentioning
confidence: 99%